PENERAPAN SANKSI ADMINISTRASI BERDASARKAN PASAL 5 PERATURAN MENTERI KEUANGAN NO: 130/PMK.010/2012 TENTANG PENDAFTARAN JAMINAN FIDUSIA TERHADAP PERUSAHAAN PEMBIAYAAN FIF GROUP CABANG PONTIANAK - FERNANDO QAMAL BUSTAMI NIM. A1012171176 (Jurnal Fatwa Hukum, 2023)
ABSTRACT This thesis discusses the application of administrative sanctions based on Article 5 of Minister of Finance Regulation Number: 130/PMK.010/2012 concerning Registration of Fiduciary Guarantees for financing companies FIF GROUP Pontianak Branch.Finance companies that provide loan financing facilities for two-wheeled motorized vehicles on credit are required to register the collateral object (two- wheeled motorized vehicles) of the debtor at the Fiduciary Registration Office located at the Regional Office of the Ministry of Law and Human Rights. The legal basis for registration of fiduciary guarantees is regulated in the Regulation of the Minister of Finance Number: 130/PMK.010/2012 concerning Registration of Fiduciary Guarantees. However, in fact, FIF GROUP Pontianak Branch as a finance company that provides consumer financing facilities in the form of special loan funds for the purchase of Honda brand two-wheeled vehicles on credit does not register fiduciary guarantees for two-wheeled motorized vehicles with credit status at the Fiduciary Registration Office located at the Regional Office. Ministry of Law and Human Rights West Kalimantan.Factors causing administrative sanctions not to be applied based on Article 5 of the Minister of Finance Regulation Number: 130/PMK.010/2012 Concerning Registration of Fiduciary Guarantees for FIF GROUP Pontianak Branch financing companies that do not register fiduciary guarantees for two-wheeled motorized vehicles with credit status due to a lack of HR to check the problem of registering two-wheeled motorized vehicles on credit as fiduciary guarantees to finance companies such as FIF GROUP Pontianak Branch. In addition, debtors who receive credit facilities for two-wheeled vehicles from FIF GROUP Pontianak Branch have never reported to the Legal Services Division of the Regional Office of the Ministry of Law and Human Rights in West Kalimantan Province regarding the registration of two-wheeled motorized vehicles on credit as fiduciary guarantees.The legal consequence for the debtor in the event that a two-wheeled motorized vehicle with credit status is not registered as a fiduciary guarantee at the Fiduciary Registration Office located at the Regional Office of the Ministry of Law and Human Rights is that a two-wheeled motorized vehicle cannot beexecuted (withdrawal) even though the debtor is in arrears of credit installments. Whereas the legal consequences for FIF GROUP Pontianak Branch who do not register fiduciary guarantees for two-wheeled motorized vehicles with credit status are that they cannot execute (withdrawal) the debtor's two-wheeled motorized vehicles if the debtor is in arrears on his credit installments. In addition, FIF GROUP Pontianak Branch may be subject to administrative sanctions as stipulated in Article 5 of Minister of Finance Regulation Number: 130/PMK.010/2012 concerning Registration of Fiduciary Guarantees, as well as criminal sanctions of confiscation due to forced execution (withdrawal) of the debtor's two-wheeled motor vehicle .The efforts that should be made by the Regional Office of the Ministry of Law and Human Rights of West Kalimantan against the finance company FIF GROUP Pontianak Branch which does not register a fiduciary guarantee for two- wheeled motorized vehicles with credit status are to provide administrative sanctions, in accordance with the provisions of Article 5 of Minister of Finance Regulation Number: 130 /PMK.010/2012 concerning Registration of Fiduciary Guarantees, if there is a report from a debtor/consumer who knows that a two- wheeled motorized vehicle with credit status is not registered as a fiduciary guarantee by the finance company FIF GROUP Pontianak Branch. Keywords: Implementation,  Administrative   Sanctions, Registration of Fiduciary Guarantees, Financing Companies.                                                                ABSTRAK Skripsi ini membahas tentang penerapan sanksi administrasi berdasarkan Pasal 5 Peraturan Menteri Keuangan Nomor: 130/PMK.010/2012 tentang Pendaftaran Jaminan Fidusia terhadap perusahaan pembiayaan FIF GROUP Cabang Pontianak.Perusahaan pembiayaan yang memberikan fasilitas pembiayaan kredit kendaraan bermotor roda dua secara kredit wajib mendaftarkan objek jaminan (kendaraan bermotor roda dua) debitur ke Kantor Pendaftaran Fidusia yang berada di Kantor Wilayah Kementerian Hukum dan HAM. Dasar hukum pendaftaran jaminan fidusia ini diatur dalam Peraturan Menteri Keuangan Nomor: 130/PMK.010/2012 tentang Pendaftaran Jaminan Fidusia. Namun faktanya, FIF GROUP Cabang Pontianak selaku perusahaan pembiayaan yang memberikan fasilitas pembiayaan konsumen berupa pinjaman dana khusus untuk pembelian kendaraan bermotor roda dua merek Honda secara kredit tidak mendaftarkan jaminan fidusia terhadap kendaraan bermotor roda dua yang berstatus kredit di Kantor Pendaftaran Fidusia yang berada di Kantor Wilayah Kementerian Hukum dan HAM Kalimantan Barat.Faktor-faktor yang menyebabkan belum diterapkannya sanksi administrasi berdasarkan Pasal 5 Peraturan Menteri Keuangan Nomor: 130/PMK.010/2012 Tentang Pendaftaran Jaminan Fidusia terhadap perusahaan pembiayaan FIF GROUP Cabang Pontianak yang tidak mendaftarkan jaminan fidusia terhadap kendaraan bermotor roda dua yang berstatus kredit dikarenakan kurangnya SDM untuk melakukan pengecekan masalah pendaftaran kendaraan bermotor roda dua secara kredit sebagai jaminan fidusia ke perusahaan pembiayaan seperti FIF GROUP Cabang Pontianak. Selain itu, debitur yang mendapat fasilitas kredit kendaraan bermotor roda dua dari FIF GROUP Cabang Pontianak tidak pernah melaporkan ke Bidang Pelayanan Hukum Kantor Wilayah Kementerian Hukum dan HAM Provinsi Kalimantan Barat mengenai pendaftaran kendaraan bermotor roda duanya secara kredit sebagai jaminan fidusia.Akibat hukum bagi debitur dalam hal kendaraan bermotor roda duanya yang berstatus kredit tidak didaftarkan sebagai jaminan fidusia pada Kantor Pendaftaran Fidusia yang berada di Kantor Wilayah Kementerian Hukum dan HAM adalah kendaraan bermotor roda duanya tidak bisa dilakukan eksekusi (penarikan) walaupun debitur menunggak angsuran kreditnya. Sedangkan akibat hukum bagi FIF GROUP Cabang Pontianak yang tidak melakukan pendaftaran jaminan fidusia terhadap kendaraan bermotor roda dua yang berstatus kredit adalah tidak bisa melakukan eksekusi (penarikan) kendaraan bermotor roda dua debitur apabila debitur menunggak angsuran kreditnya. Selain itu, FIF GROUP Cabang Pontianak dapat dikenakan sanksi administratif sebagaimana diatur dalam Pasal 5 Peraturan Menteri Keuangan Nomor: 130/PMK.010/2012 tentang Pendaftaran Jaminan Fidusia, serta sanksi pidana perampasan karena melakukan eksekusi (penarikan) kendaraan bermotor roda dua debitur secara paksa.Adapun upaya yang seharusnya dilakukan oleh Kantor Wilayah Kementerian Hukum dan HAM Kalimantan Barat terhadap perusahaan pembiayaan FIF GROUP Cabang Pontianak yang tidak mendaftarkan jaminan fidusia terhadap kendaraan bermotor roda dua yang berstatus kredit adalah memberikan sanksi administratif, sesuai dengan ketentuan Pasal 5 Peraturan Menteri Keuangan Nomor: 130/PMK.010/2012 tentang Pendaftaran Jaminan Fidusia, apabila terdapat laporan dari debitur/konsumen yang mengetahui bahwa kendaraan bermotor roda duanya yang berstatus kredit tidak didaftarkan sebagai jaminan fidusia oleh perusahaan pembiayaan FIF GROUP Cabang Pontianak. Kata Kunci : Penerapan,Sanksi  Administrasi, Pendaftaran Jaminan Fidusia, Perusahaan Pembiayaan.